A Single-Center Detection of Adult Patients with Advanced Periodontal Disease Using Surgical Assessment and Cone-Beam Computed Tomography - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:One of the major limitations of conventional radiological procedures is the presence of considerable overlapping and lack of clear, three-dimensional information. Cone-beam computed tomography (CBCT) has emerged as an effective imaging modality in such situations offering high-quality images and lower radiation exposure to patients.Aim:The aim of the present study was to assess the role of CBCT in the detection of intra-bony defects in patients with advanced periodontal disease.Settings and Design:The present study was designed as a prospective, observational study wherein patients aged between 35–55 years with advanced periodontal disease who were indicated for periodontal treatment in form of periodontal surgeries were selected from the outpatient department (OPD) based on defined inclusion and exclusion criteria.Materials and Methods:Sixty patients with chronic periodontitis with 12 teeth each including 6 anterior and 6 posterior teeth were selected for making measurements pre- and peri-operatively while bone defects were measured first with the help of CBCT software installed in an individualized system devised to be used for storing and analyzing CBCT images and then, during surgical intervention using standardized UNC-15 periodontal probe and compared.Statistical Analysis Used:Statistical analysis was performed using SPSS version 18.0 (SPSS Inc., Chicago, IL, USA). The measurements obtained with the help of CBCT software installed in the personalized system and those obtained on surgical exploration were compared in each anterior and posterior tooth with the help of paired-sample t-test while Pearson's correlation(r) was used to test the correlation between the observed values. The level of statistical significance was set atP< 0.05.Results:The results were found to be highly significant both in terms of statistical (P-value) and clinical (r) significance for various sites in the anterior and posterior teeth in all instances.Conclusions:From the observations made from the present study, it could be concluded that CBCT provided highly precise assessment of bone topography equivalent to the judgment obtained during surgical exposure at the sites of interest preoperatively, which helped in assessing the exact type and depth of defect present and helped in optimizing surgical treatment planning.